The concept of corruption: an overview of the past and present scenarios - Wan Hashim, Wan Murshida; Muhamad Hussain, Mazlena (Faculty of Administrative Science and Policy Studies, 2024)
Corruption is neither an old nor a new phenomenon and it has been around the globe for centuries since the existence of human civilizations. Corruption can be found everywhere regardless of state, country, system, race, culture as well as religion. To understand the concept of corruption as a timeless phenomenon, this paper discusses the matter by tracing the development of it started from the historical period of ancient civilization until present. The discussion is sub-divided into two eras i.e., pre-modern period and modern period. This article applied the qualitative research method which is in the form of document analysis. The primary and secondary data were collected from relevant documents concerning corruption such as statutes, decided cases, journal articles, books, magazines, newspaper cuttings, media reports, and blogs. The findings indicate that corruption, which has been in existence since time immemorial, happened all over the world and it comes in many forms and types. Despite exposure and harsh punishments being imposed upon perpetrators, corruption is still persistent. This means that corruption is not an easy problem to tackle, and laws alone could not be the only solution. Hence, cooperation from every member of society should be given emphasis in the fight against corruption so that corruption can finally be defeated.